2023
DOI: 10.1111/myc.13565
|View full text |Cite
|
Sign up to set email alerts
|

Does metabolite matter? Defining target itraconazole and hydroxy‐itraconazole serum concentrations for blastomycosis

Abstract: Background: Itraconazole is the recommended first-line treatment for mild-tomoderate blastomycosis and consolidation treatment of moderate-to-severe disease.Itraconazole is metabolised into three metabolites, including an active metabolite hydroxy-itraconazole. Literature provides little evidence indicating whether therapeutic drug monitoring targets should be based on itraconazole parent compound alone or a sum of itraconazole and hydroxy-itraconazole serum concentrations.Objectives: This study aims to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…In patients with oropharyngeal candidiasis, itraconazole serum concentrations <1.0 mcg/mL were associated with treatment failures [103]. A recent study has shown that subtherapeutic concentrations (<1.0 mcg/mL) of itraconazole and hydroxyitraconazole were associated with increased mortality in patients with blastomycosis [104]. It is unclear if a concentration above 1.0 mcg/mL of the parent drug (itraconazole) or a combination of parent drug + metabolite (Itraconazole/hydroxyitraconazole) is required for improved outcomes in the management of histoplasmosis.…”
Section: Managementmentioning
confidence: 99%
“…In patients with oropharyngeal candidiasis, itraconazole serum concentrations <1.0 mcg/mL were associated with treatment failures [103]. A recent study has shown that subtherapeutic concentrations (<1.0 mcg/mL) of itraconazole and hydroxyitraconazole were associated with increased mortality in patients with blastomycosis [104]. It is unclear if a concentration above 1.0 mcg/mL of the parent drug (itraconazole) or a combination of parent drug + metabolite (Itraconazole/hydroxyitraconazole) is required for improved outcomes in the management of histoplasmosis.…”
Section: Managementmentioning
confidence: 99%